Unusual presentation of urban leptospirosis complicated by a septic shock. (2019) - El Hasbani, Georges; Farooqui, Sarmad Riaz; Kofahi, Ahmad; Saeed, Yasir; Tayeh, Omar; Abu-Hishmeh, Mohammad; Moran, Herbeth; Troya-Maldonado, Marcelo; Khanna, Rajan; Assaker, Jean-Pierre; Assaker, Richard
Abstract: Leptospirosis, an infectious zoonosis, is common to tropical areas. The clinical presentation varies from flu-like symptoms to a serious presentation called Weil's syndrome. Fever and conjunctival suffusion are present in the majority of patients. This case report describes a resident of New York City who presented initially with gastroenteritis symptoms without fever or conjunctival suffusion to develop septic shock before being diagnosed with leptospirosis.